Design and Build of a Solar Panel Integration Dryer and Temperature Controller with Autocad Inventor - Nalendro Mataram; Muhammad Dimas Adjie; Anis Nurrohkayati (Procedia of Engineering and Life Science, 2021)
Drying is a mandatory process carried out after harvest or production. Direct drying is a traditional method that is still used today, but this method has drawbacks because it depends on the weather. Pests, the rainy season, and at night are obstacles experienced in this process. This dryer can help solve common solutions for manufacturers. A dryer coated with clear acrylic it can protect the produce from rain, dust, and pests. The solar panel functions as a power source for the temperature controller in the dryer. 40-50 C is the right temperature when drying, it is not recommended that temperatures exceed 50 because it can cause dry food ingredients outside. Incandescent lamps and mini fans are temperature control devices to stabilize the temperature inside with temperatures of 40 ̊ to 50 C. Incandescent lamps also allow manufacturers to dry at night so that the drying process can be shorter than usual. The result found by the dryer is that it has a cross-sectional area of ​​2100 cm2 with a maximum capacity of 13 pieces with a diameter of 7 cm. The drying rate with the sun reaches 0.6% per hour, and the energy needed by the sun for 10 hours of drying is 36288 kJ. The power that can be produced by solar panels is 100 watts with the electrical energy needed for 10 hours of drying with a controller of 3600J.